A high‐yielding CHO transient system: Coexpression of genes encoding EBNA‐1 and GS enhances transient protein expression. (10th October 2013) - Daramola, Olalekan; Stevenson, Jessica; Dean, Greg; Hatton, Diane; Pettman, Gary; Holmes, William; Field, Ray
<x xml:space="preserve">Abstract</x> An efficient rapid protein expression system is crucial to support early drug development. Transient gene expression is an effective route, and to facilitate the use of the same host cells as for subsequent stable cell line development, we have created a high‐yielding Chinese hamster ovary (CHO) transient expression system. Suspension‐adapted CHO‐K1 host cells were engineered to express the gene encoding Epstein‐Barr virus (EBV) nuclear antigen‐1 (EBNA‐1) with and without the coexpression of the gene for glutamine synthetase (GS). Analysis of the transfectants indicated that coexpression of EBNA‐1 and GS enhanced transient expression of a recombinant antibody from a plasmid carrying an OriP DNA element compared to EBNA‐1‐only transfectants. This was confirmed with the retransfection of an EBNA‐1‐only cell line with a GS gene. The retransfected cell lines showed an increase in transient expression when compared with that of the EBNA‐1‐only parent. The transient expression process for the best CHO transient cell line was further developed to enhance protein expression and improve scalability by optimizing the transfection conditions and the cell culture process. This resulted in a scalable CHO transient expression system that is capable of expressing 2 g/L of recombinant proteins such as antibodies. This system can now rapidly provide gram amounts of recombinant antibody to supply preclinical development studies that has comparable product quality to antibody produced from a stably transfected CHO cell line. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:132–141, 2014